Off-Piste Skiing Demand Patterns and Climate Change Adaptation Pathways in La Grave, France - Nao Yoshizawa; Jonathan Cognard; Lucas Berard-Chenu; Philippe Bourdeau (Mountain Research and Development)
Off-piste skiing is an adventurous niche segment of ski tourism that is gaining in popularity. However, its demand dynamics remain unclear. This study aimed to elucidate daily off-piste skiing demand patterns by developing a regression model for La Grave, located in the French Alps, where all visitors engage in off-piste skiing. We found that the amount of fresh snow positively influenced skier visits and forecasted avalanche risk did not affect skier visits. Vacation periods did not positively influence skier visits, whereas the post-COVID period has had a negative effect. We also discuss the impact of climate change and adaptation strategies in the area. La Grave depends heavily on off-piste skiing. Because one of the purposes of this activity is to ski on fresh natural snow, it cannot rely on snow management practices such as grooming and snowmaking, which are widespread adaptations in conventional ski areas. The winter business model in La Grave is expected to face further challenges in the future because of climate change. In addition, both a new development plan and opposition movements have emerged. La Grave appears to be undergoing a transition away from a model heavily dependent on off-piste skiing.